Multicenter retrospective cohort study demonstrates superior safety profile of indobufen over aspirin for Post-CABG antiplatelet therapy - Ren, Yu; Zhu, Yanwu; Yan, Qiaoyan; Jin, Hui; Luo, Hua (Frontiers in Pharmacology, 2024)
Objectives: Coronary artery bypass grafting (CABG) is essential for treating coronary artery disease, with postoperative aspirin crucial to prevent graft restenosis. However, its gastrointestinal side effects may limit tolerability in some patients. Indobufen presents a potential alternative, but its safety and efficacy need further validation. This study aimed to compare the efficacy and safety of indobufen versus aspirin in patients’ post-CABG. Methods: This retrospective observational study included 39 patients who underwent CABG at two centers from January to December 2023. Patients were retrospectively assigned to two groups based on the antiplatelet therapy they received: the indobufen group (n=19) and the aspirin group (n=20). The primary endpoint was a composite of non-fatal myocardial infarction, stroke, and revascularization due to acute coronary syndrome in the intention-to-treat population. Postoperative data on platelet count, hemoglobin, D-dimer, activated partial thromboplastin time (APTT), and hospital stay length were collected. Transfusion rate, bleeding, thrombotic events, and gastrointestinal adverse reactions were compared between the two groups. Results: Over the 8-to-18-month follow-up period, 5 patients (25%) in the aspirin group reached the primary endpoint, while none in the indobufen group did, a difference that was statistically significant (P = 0.02). Although the rates of non-fatal myocardial infarction, revascularization, stroke, and thrombotic events were higher in the aspirin group, these differences did not reach statistical significance. Importantly, the total bleeding events were markedly lower in the indobufen group (15.79% vs. 55%, P = 0.011), with major bleeding events also significantly reduced in the indobufen group (0% vs. 20%, P = 0.04). Both groups showed no significant differences were observed in postoperative hospital stay, hemoglobin, and D-dimer levels between the groups. However, the indobufen group demonstrated significantly lower platelet count and APTT. The average daily cost of indobufen was 27.8 times higher than that of aspirin. Conclusion: Indobufen demonstrates a comparable antiplatelet effect to aspirin and offers significant advantages in reducing gastrointestinal adverse reactions and bleeding risk. It can be considered a preferable alternative for patients who cannot tolerate or have contraindications to aspirin. Further large-scale clinical trials are needed to confirm its potential as the first-choice antiplatelet therapy post-CABG.